The level of instructional design skills for art education teachers in the Sabya Education Directorate, and the effectiveness of a proposed training Program for their development - Nouhi, Malhya Ahmad Ali (Journal of Educational and Psychological Sciences, 2022)
The research aimed to know the level of instructional design skills among art education teachers in the Sabya Education Department, in addition to revealing the effectiveness of the training program in developing the cognitive and performance aspects of instructional design skills. To achieve the research objectives, the descriptive and experimental approaches were used; While the two research tools were represented in the achievement test to measure the cognitive aspect, which consisted of (24) questions at three levels (remembering, understanding and application), and the observation card to measure the performance aspect of the educational design skills consisted of (55) behavioral sub-phrases distributed on five main skills, namely (analysis, The design, development, implementation, and evaluation) were applied to a simple random sample of (30) teachers of art education in the Sabya Education Department. The research concluded that the level of educational design skills as a whole in the diagnostic research sample was weak; Where the skills got a general arithmetic average of (67.7 out of 165), and on the skill level, the arithmetic mean was for the analysis skill (14.03 out of 33), for the design skill it reached (14.2 out of 36), for the development skill (14.4 out of 36), and for the implementation skill (10.9 out of 36). 27), and assessment skill (14.16 out of 33). The results also showed a significant effectiveness of the proposed program in developing the cognitive aspect of instructional design skills; The effect size (d) of the program in developing the cognitive aspect as a whole was (2.47), while it reached the levels of (remembering, applied comprehension) respectively (1.36; 0.84; 1). It was also clear that the proposed program was highly effective in developing the performance aspect of instructional design skills; Where the effect size (d) of the program in the development of the performance aspect as a whole was (2.75), while it reached for skills (analysis, design, development, implementation, evaluation) respectively (2.4; 2.44; 2.74; 2.47; 2.55), and based on the results recommended The researcher, officials of the Sabya Education Department, are interested in increasing training programs related to educational design skills to train art education teachers on them to help them design and build traditional or electronic courses, in addition to proposals for future studies on the subject.
Keywords: Training Program; Instructional Design Skills